1972
DOI: 10.1037/h0033639
|View full text |Cite
|
Sign up to set email alerts
|

Free recall of grouped words.

Abstract: Grouped and ungrouped lists were presented for free recall. Temporal grouping increased recall of only items presented at the end of the list, i.e., shortterm storage. Contrary to expectations, grouping did not improve long-term storage. The fact that grouping produced a stereotypic order of recall focused on recall order as a crucial factor in determining short-term recall.Grouping is interesting not only because it is used frequently as a mnemonic technique but also because it is intimately involved in speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

1976
1976
1989
1989

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
3
15
1
Order By: Relevance
“…(2) Otherwise, no major effects were The first experiment was carried out to see whether recall from STS could be improved by varying the order of recall. Much evidence (Gianutsos, 1970;Posner, 1964;Tulving & Arbuckle, 1963) exists to support the hypothesis that the amount a subject recalls depends on the order in which items are to be recalled. The contention is that the act of recalling old items has the effect of displacing information from STS in much the same manner that taking in additional list items does.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Otherwise, no major effects were The first experiment was carried out to see whether recall from STS could be improved by varying the order of recall. Much evidence (Gianutsos, 1970;Posner, 1964;Tulving & Arbuckle, 1963) exists to support the hypothesis that the amount a subject recalls depends on the order in which items are to be recalled. The contention is that the act of recalling old items has the effect of displacing information from STS in much the same manner that taking in additional list items does.…”
Section: Resultsmentioning
confidence: 99%
“…Temporal (rhythmical) grouping is such a procedure. Gianutsos (1972) showed that, when lists were presented in temporal groups of three words, words were recalled in order within the last two groups, starting With the last group, and the STS component was substantially increased. The present view is that techniques, such as temporal grouping or the present procedure, improve retrieval from STS and do not affect LTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, any sublist primacy and recency effects could occur due to extra rehearsal of the first or last few items of each sublist (e.g., Gianutsos, 1972). To control for this possibility, subjects were instructed to rehearse out loud only the most recently presented set of five words during each 15-s delay period.…”
Section: Methodsmentioning
confidence: 99%
“…If inserting pauses into a presentation facilitates chunking or conjoining, then inserting pauses into a presentation should improve free recall. Instead, inserting pauses into a presentation does not improve free recall (Gianutsos, 1972).…”
Section: Chunkingmentioning
confidence: 99%